PENGARUH TINGKAT SUKU BUNGA PINJAMAN, DENDA PENYALURAN, KAPASITAS KREDIT (ALOKASI DANA) DAN RASIO NON PERFORMING LOAN TERHADAP PENYALURAN KREDIT USAHA MIKRO DAN KECIL (KUMK) - , Lutfi Anwari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Kredit Usaha Mikro dan Kecil (KUMK) is productive credit channeled by financial institution to micro and small enterprises. KUMK is the implementation of government programs. The mechanism of the program is that the government provides the funds as a loan to a designated financial institution and afterward the financial institution will use the fund to provide loans for micro and small enterprises. In practice, the KUMK distribution not optimized. It is show with on average only 59% of financial institutions capable of delivering KUMK appropriate targeted by the government, while the remaining 41% cannot afford. In order to encourage increased distribution of KUMK, the government should have knowledge of the factors that may affect the KUMK distribution, in specially factors controlled by government. Therefore, in this study will be tested factor from government policy. These factors are interest rate, the penalty of KUMK distribution, credit capacity and non-performing loan of KUMK. The analysis model of the significance test used in this research is the ordinary least square. Based on purposive sampling method, the data used in this research is the data sample of 23 financial institutions from the total 32 financial institutions designated by the government for disbursing the KUMK funds. Period of observation is February 2005 until December 2010. This research concludes that simultaneous the interest rates of KUMK, the distribution of penalty, the allocation of program funds and the non-performing loan ratio of KUMK effect significantly the amount of the disbursed KUMK, but partially only SBI the interest rates of KUMK that has significant influence, whereas other variables show no significant results. Government can use the interest rates of KUMK as the instrument to affect the distribution of KUMK effectively. In order to effectiveness the penalty of KUMK distribution, the government can evaluate the tariff in determining the amount of penalty and, implementation of the reduction of program funds to financial institutions which provided penalty for two consecutive quarters. The use of monthly adjusted data of quarterly data for the variable distribution penalty variable is a limitation in this study